Model Literasi Ekologi Integratif Berbasis Komunitas untuk Mahasiswa Calon Guru Biologi: Desain, Implementasi, dan Evaluasi - Sari, Rangga; Saputra, Andi (Lembaga Publikasi Ilmiah Nusantara, 2025)
Strengthening ecological literacy is an urgent necessity in pre-service biology teacher education, given the increasing complexity of environmental challenges and the demands of 21st-century learning. This study aims to develop and evaluate an Integrative Community-Based Ecological Literacy Model designed to enhance students’ conceptual understanding, critical thinking skills, and ecological awareness. The model integrates project-based learning, field experiences, and active collaboration with local communities as authentic learning resources. A mixed-methods research design was employed, consisting of needs analysis, model development, implementation, and evaluation stages. Data were collected through ecological literacy tests, observations, interviews, and analysis of students’ project outputs. The findings indicate that the model effectively improves students’ holistic understanding of ecological concepts, strengthens their analytical abilities in addressing environmental issues, and fosters active participation in community-based conservation activities. These results highlight that integrating community contexts into ecological learning enriches the learning process and optimizes the role of pre-service biology teachers as agents of environmental change. The developed model is recommended for adaptation in various educational contexts that emphasize environmental sustainability.